Institutionalizing Women Empowerment in Nigeria: The Contributions of the Federal Ministry of Women Affairs to Sustainable Development - Osegboun, Adebola Esther (Atlantis)

(untitled) (Mount Saint Vincent University, 2025)
Women empowerment is an indicator of social change and an important goal in achieving sustainable development worldwide (United Nations n.d.). Historically and across nations until today, men have had greater access to power and resources and more socio-politico-economic opportunities. In Nigeria, the plights of women are becoming more appalling as men are properly positioned to benefit and advance professionally and socially. Women in Nigeria need to be empowered because their contributions to national development is far too significant to be ignored. While literature abounds on women empowerment in Nigeria, there is a dearth of research on the contributions of the Federal Ministry of Women Affairs and Social Development (FMWASD) to women empowerment. It is against this background that this article examines the contributions of the FMWASD to sustainable development in Nigeria through its various women empowerment efforts from 2011-2021. This work is expected to contribute to the efforts to raise public and government attention to the need to foster women’s agency and for the government to be able to deliver on its mandate.